Role of multidetector CT virtual cystoscopy compared to conventional cystoscopy in the diagnosis of urinary bladder neoplasms - Gamal Niazi; Waleed M. Hetta (The Egyptian Journal of Radiology and Nuclear Medicine, 2019)
Abstract Background The study was done to assess the utility of multidetector CT virtual cystoscopy versus conventional cystoscopy in the diagnosis of urinary bladder tumors. Thirty patients were included, 23 patients with recently diagnosed bladder masses, 7 patients with history of previously resected bladder masses. Conventional cystoscopy was done to all patients with biopsy of suspicious lesions. CT examinations were performed with a 16 and a 320-MDCT scanners. Multiplanar reconstructed (MPR) images were obtained. Also virtual cystoscopic images were obtained with the volume rendering technique and the same software used for MPR images. Results CTVC detected 9 out of 10 polypoid masses detected by conventional cystoscopy (90% sensitivity), 23 out of 23 sessile masses (100% sensitivity), 4 out of 4 areas of wall thickening (100% sensitivity), and 0 out of 1 case mucosal color change (0% sensitivity). Conclusion CTVC is a minimally invasive technique that can be of value for primary diagnosis, surveillance and screening of urinary bladder neoplasms.